Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1177/1541204009361177
|View full text |Cite
|
Sign up to set email alerts
|

Contexts of Decision Making in the Juvenile Justice System: An Organizational Approach to Understanding Minority Overrepresentation

Abstract: Significant advances have been made in our understanding of the origins and dynamics of minority overrepresentation in the juvenile justice system. Nevertheless, much remains to be learned. In this article, the authors explore the impact of race on juvenile justice processing by examining the organizational contexts in which decisions are made. They offer a theoretical framework that combines insights from organizational theory and the focal concerns perspective and that focuses on the organizational players (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
225
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(258 citation statements)
references
References 72 publications
(75 reference statements)
18
225
4
Order By: Relevance
“…Minorities charged with an alcohol/drug offense also increased the chances of detention. The latter finding is consistent with both the symbolic threat perspective and prior research, whereby minority youth are perceived by decision makers as more delinquent, dangerous, and as drug offenders than Whites (e.g., Bishop et al, 2010;Snyder, 1990;Steen, Engen, & Gainey, 2005).…”
Section: Multivariate Results Involving Initial Detention Decisionsupporting
confidence: 88%
See 1 more Smart Citation
“…Minorities charged with an alcohol/drug offense also increased the chances of detention. The latter finding is consistent with both the symbolic threat perspective and prior research, whereby minority youth are perceived by decision makers as more delinquent, dangerous, and as drug offenders than Whites (e.g., Bishop et al, 2010;Snyder, 1990;Steen, Engen, & Gainey, 2005).…”
Section: Multivariate Results Involving Initial Detention Decisionsupporting
confidence: 88%
“…Rodriguez argues that the less severe treatment of African American youths at detention reflects a ''self-correction'' process, where ''juvenile court officials may be compensating for proactive arrest policies'' (p. 649). A similar interpretation of decision making involving a correction factor on the part of juvenile court personnel for disparities at earlier stages in the proceedings has been offered elsewhere (e.g., Bishop et al, 2010;Leiber, 1994) and highlights the complexity of decision making in the juvenile justice system and the contextual nature of race.…”
Section: Prior Researchmentioning
confidence: 81%
“…For example, it was noted that older non-white youth were more likely to receive pre-dispositional secure detention after JDAI's adoption which is consistent with some prior research on the topic. Bishop, Leiber, & Johnson (2010) found that older African-American youth were more likely to be referred to court, and Leiber and Johnson (2008) found that African-Americans did not receive leniency in processing based on age whereas white juveniles were afforded a "youth discount." With the greater emphasis placed on legal variables after the adoption of JDAI, we would not expect age to affect whether a juvenile receives secure detention.…”
Section: Discussionmentioning
confidence: 99%
“…Results showed that African Americans were .60 times less likely to be informally processed after arrest, 1.49 times more likely to be detained pre-adjudication, and 1.7 times more likely to be placed out of the home than European Americans. The disproportionate and severe outcomes for African Americans, particularly males, in the juvenile justice system have been substantiated in many other studies (e.g., Bishop, Leiber, & Johnson, 2010;Carmichael & Burgos, 2011;Leiber, Brubaker, & Fox, 2009;Leiber & Johnson, 2007). These data on disproportionality warrant a "call to action" in research and policy (Lichtenstein, 2009, p. 252).…”
mentioning
confidence: 82%